The present‐day stress field in the Zagros Fold-Thrust Belt of Iran, from inversion of focal mechanisms. (January 2021) - Khanban, Mohammad Ali; Pakzad, Mehrdad; Mirzaei, Noorbakhsh; Moradi, Ali; Mehramuz, Mahmoud
Abstract: The knowledge about spatial variation of stress field is an important step in the identification of geodynamic and seismotectonic characteristics. Inversion of focal mechanism solutions is one of the most common methods for determination of stress field and the shape ratio in a tectonic region. In this paper, Iterative Joint Inversion method is used to determine principal stress axes from earthquake focal mechanisms in the Zagros continental collision zone of Iran. In order to determine the influence of dependent events on the inversion results, the declustering process is carried out by the Urhammer's method. The area is divided into seven subzones according to the stress field heterogeneity in the Zagros region. In each subzone, the trends of principal stress axes, the orientation of maximum horizontal stress, stress regime and the shape ratio are determined. The results show that the compressional stress direction averages NNE-SSW that accord with the current convergence between the Arabian plate and Iranian micro-continent. A gradual counterclockwise rotation of the compressional axis is also concluded which is compatible with spatial changes in the Arabian–Eurasian convergence paths along the Zagros. The stress regime of most of the subzones is deduced as the Transpression that reflects oblique convergence. The orientation of the maximum principal stress ( σ 1 ) show the lowest uncertainty in respect to the intermediate ( σ 2 ) and minimum ( σ 3 ) principal stress axes. The shape ratio error in all zones are less than 6 and 7.2 percent before and after implementing exclusion respectively, which indicate this error increases with removing the dependent events in all zones except for zone 3.